Experimental Validation of the Biomechanical Response of an Anthropo-morphic Testing Device (Dummy) at Low Impact Velocities - Jelen, Karel; Kubovy, Petr; Lopot, Frantisek; Fara, Lukas; Jezdik, Roman; Hrusa, Filip; Purs, Hynek; Tikkanen, Tommi; Novak, Martin; Svoboda, Martin; Tomsovsky, Lubos (Manufacturing Technology Journal, 2023)
The paper describes the experimental validation of the biomechanical response of the Hybrid III 50th Percentile Male Pedestrian Dummy (JASTI, Tokyo, Japan) at low impact velocity (up to 2.2 m/s) in comparison with that of human probands. The paper is based on previous research that was focused on the tram-pedestrian crash tests using the same dummy. The biofidelity of the dummy was analyzed in two collision scenarios: the anteroposterior impact (chest impact) and lateral impact (shoulder impact) using a unique pendulum impact testing machine of own design and construction. The primary outcome variable was the peak resultant acceleration of the head and chest during the impact. Based on the lab-based measurements, the unique impact testing machine was found adequate and precise for the purposes of future crash-test analyses in the area of the automotive industry. The proposed methodology and measurement protocol were shown proper to compare the data between the dummy and human participants. Following the pilot experiments, the kinematic and dynamic data between the dummy and human participants were analyzed to assess the biofidelity of the dummy for the frontal and side impact during tram-pedestrian collisions at low impact velocities.
Keywords: Crash test; Tram; Pedestrian; Safety; Dummy; Biofidelity